Assessment of Life Cycle Risks of Deconstruction in Urban Regeneration Projects - Koc, Kerim; Okudan, Ozan (ASCE-AMER SOC CIVIL ENGINEERS, 2021)
Deconstruction is the eco-friendly alternative to demolition. It can help reduce the waste stream from urban regeneration projects (URPs) to landfills. The literature, however, does not provide a sufficient theoretical basis in terms of life cycle and life cycle risks of deconstruction. This lacking presents a major roadblock to its implementation in URPs. Thus, this paper introduces the deconstruction life cycle and a risk management framework to guide construction practitioners. Initially, the deconstruction life cycle, comprising 9 phases and 55 risk factors, was identified through a literature review and a focus group discussion. Then, a fuzzy analytical hierarchy process (AHP) was conducted to assess the impact of each risk on deliverables of deconstruction. Results showed that risk management in deconstruction should be a cyclic process and cover the entire life cycle. Risks related to inaccurate estimations, quality, health and safety issues, insufficiency of building components to reuse and recycle, unavailability of deconstruction contractors, and lack of infrastructure were among the most significant risks of deconstruction. By revealing the life cycle and life cycle risks of deconstruction, this study highly contributes to theory as well as significant managerial implications.
Keywords: Deconstruction; Urban regeneration; Demolition waste; Fuzzy analytical hierarchy process; Risk management; ANALYTICAL HIERARCHY PROCESS; FUZZY AHP APPROACH; REVERSE LOGISTICS; BUILDING DECONSTRUCTION; SUPPLY CHAIN; FOCUS GROUP; CONSTRUCTION; MANAGEMENT; MODEL; Construction & Building Technology; Engineering